Broadening Participation in STEM College Majors: Effects of Attending a STEM-Focused High School - Barbara Means; Haiwen Wang; Xin Wei; Emi Iwatani; Vanessa Peters (SAGE Publishing, 2018)
To increase participation in science, technology, engineering, and mathematics (STEM) studies and careers, some states have promoted inclusive STEM high schools. This study addressed the question of whether these high schools improve the odds that their graduates will pursue a STEM major in college. State higher education records were obtained for students surveyed as seniors in 23 inclusive STEM high schools and 19 comparison schools without a STEM focus. Propensity score weighting was used to ensure that students in the comparison school sample were very similar to those in the inclusive STEM school sample in terms of demographic characteristics and Grade 8 achievement. Students overall and from under-represented groups who had attended inclusive STEM high schools were significantly more likely to be in a STEM bachelor's degree program two years after high school graduation. For students who entered two-year colleges, on the other hand, attending an inclusive STEM high school was not associated with entry into STEM majors.